Simulating air distribution and occupants' thermal comfort of three ventilation schemes for subway platform. (15th November 2017) - Liu, Changping; Li, Angui; Yang, Changqing; Zhang, Wenrong
Abstract: Excellent air distribution is an indispensable factor to acquire comfortable environment in high density occupant areas, such as subway stations. This study assesses the air distribution by adopting three different air supply schemes (mixing ventilation, stratified air ventilation and air curtain ventilation) for a subway platform. The simulation results are discussed in detail by considering air velocity, air temperature, age of air and Relative Warmth Index (RWI). It was demonstrated that air curtain ventilation presented an appropriate velocity and temperature distribution, which provides a healthy and comfortable environment. Focusing on the air curtain ventilation scheme, four cases were investigated to indicate the air velocity and temperature distribution in the occupied region. It is indicated that the highest velocities and the lowest temperatures were both achieved at the height of 0.2 m above the floor. Dimensionless velocity with different air supply velocity was proposed in this paper. This research is applicable for air curtain ventilation design appropriate for subway platform. Highlights: Air distributions in occupied region of platform were carried out under mixing ventilation, stratified air ventilation and air curtain ventilation. The dimensionless velocity decreases were acquired and compared for selection of ventilation scheme. Supply air velocity in air curtain ventilation was optimized to improve the comfort level in occupied region. This study can be used in designing the air curtain ventilation for a subway platform.